D-Pen: Pen reader for dyslexia students - Che Daud, Norhayati; Mohd Nazar , Ahmad Azahari; Abdullah, Mazlinda; Muhd Fadzludin, Isyraq Nur Hazriq (Environment-Behaviour Proceedings Journal, 2024)
Dyslexia, a persistent neurodevelopmental disorder, challenges reading, spelling, and language processing. Early identification of phonological processing issues is crucial, demanding tailored interventions for sustained academic success. An innovative solution involves using a multipurpose smartpen reader with audio capabilities that connect to smartphones. It uses optical character recognition (OCR) to digitise printed text for transfer to devices, enhancing accessibility. The added features of audio narration, pop art design, and a portable scanner with autocorrection contribute to a comprehensive tool addressing the needs of various dyslexic students during learning activities.